The Successful Manager's Guide to 1992 : Working in the New Europe - Featherstone, Kevin (London Fontana/ Collins, 1990)
After 1992, Europe becomes a single market. It is an unprecedented business opportunity and this book explores how the new Europe will affect both the private and public sectors. It also looks at the economic and legal aspects of the change as well as the individual citizen's rights.
Include Appendix and Index
Keywords: Europe -- Europe--European Economic Community countries -- Economic history -- Economic policy